War for profit : Army contracting vs. supporting the troops - Smith, Charles M. (Contracts manager) (Algora Pub., 2012)
"WASHINGTON - The Army official who managed the Pentagon's largest contract in Iraq says he was ousted from his job when he refused to approve paying more than 1 billion in questionable charges to KBR ..." (James Risen, New York Times, June 17, 2008). This book by that very Army official provides an eye-opening firsthand account of how the US Government hands over your tax dollars to support contractors like KBR and Halliburton, rather than supporting the troops. This authoritative and well-documented record of the LOGCAP contract in Iraq and Afghanistan is at the same time a study of US parti.